Toutes directions: reading the signs in an urban sprawl - Geertz, Clifford (International journal of Middle East studies, 1989)
The article discusses the struggle in Sefrou, an "Islamic" city south of Fez, between 1976 and 1986 over different concepts of how a city should look, how and by whom it should be governed, who should live in it, what its life should be, where its center should lie, its expanse be segmented, and its boundaries be placed. The recent history of Sefrou illuminates the increasing difficulty of defining the idea of "the Islamic City". (DÜI-Hns)